Postoperative biochemical remission of serum calcitonin is the best predictive factor for recurrence‐free survival of medullary thyroid cancer: a large‐scale retrospective analysis over 30 years. (30th July 2015) - Jung, Kyong Yeun; Kim, Seok‐Mo; Yoo, Won Sang; Kim, Bup‐Woo; Lee, Yong Sang; Kim, Kyung Won; Lee, Kyu Eun; Jeong, Jong Ju; Nam, Kee‐Hyun; Lee, Se Hoon; Hah, Jeong Hun; Chung, Woong Youn; et al.
Summary: Context: The increase in thyroid screening in the general population may lead to earlier detection of medullary thyroid carcinoma (MTC). Objective: We aimed to evaluate secular trends in clinicopathological characteristics and long‐term prognosis of MTC and its prognostic factors. Design: This was a retrospective analysis from 1982 to 2012. Patients: Three hundred and thirty‐one patients with MTC were included and grouped based on the year of diagnosis (1982–2000, 2001–2005, 2006–2010 and 2011–2012). Measurements: These included recurrence and mortality as well as biochemical remission (BCR) of serum calcitonin. Results: Mean tumour size (from 2·5 cm to 1·7 cm, P < 0·001) and percentage of extrathyroidal extension (from 52·0% to 26·0%, P = 0·026) decreased. The percentage of patients achieving BCR within six postoperative months (po‐BCR) increased with time (from 39·6% to 76·1%, P < 0·001). The 5‐year overall recurrence rate significantly decreased in 2006–2012 compared to 1982–2005 (10% vs 18%, respectively, P = 0·031), although the 5‐year survival rate did not improve (92% vs 92%, P = 0·929). Failure to achieve po‐BCR was the strongest predictive factor associated with recurrence (hazard ratio [HR] = 58·04, 95% CI 7·14–472·11; P < 0·001). Male gender (HR = 3·18, 95% CI 1·18–8·56; P = 0·022), tumour size >2 cm (HR = 18·33, 95% CI 2·35–143·06; P = 0·006) and distant metastasis (HR = 4·00, 95% CI 1·31–12·21; P = 0·015) were significant prognostic factors for mortality. Conclusions: Clinicopathological characteristics and recurrence of MTC improved with time. Po‐BCR was the best predictive factor for recurrence‐free survival.